Abdominal paraganglioma in a young woman with 1p36 deletion syndrome. Issue 2 (24th October 2016) - Murakoshi, Miki; Takasawa, Kei; Nishioka, Masato; Asakawa, Masahiro; Kashimada, Kenichi; Yoshimoto, Takanobu; Yamamoto, Toshiyuki; Takekoshi, Kazuhiro; Ogawa, Yoshihiro; Shimohira, Masayuki
Abstract : 1p36 deletion syndrome is the most common terminal deletion syndrome, and the genomic regions that contribute to specific 1p36 deletion syndrome‐related phenotypes were recently identified. Deletions in the 1p36 region have been documented in various tumor tissues, which indicates correlation between loss of heterozygosity of 1p36 and tumor development, and the existence of tumor suppressors in this region. Therefore, it was suspected that patients with 1p36 deletion syndrome have a higher risk of tumor development; however, only a few child cases of neuroblastoma with 1p36 deletion syndrome have been reported. We report the first case of 1p36 deletion syndrome with paraganglioma (PGL) and include genetic investigation. The 24‐year‐old woman with 1p36 deletion syndrome had severe intellectual disability, dilated cardiomyopathy, and distinct dysmorphic features, and presented with persistent vomiting accompanied by hypertension (178/115 mmHg). Abdominal CT revealed a 40 × 50 mm retroperitoneal mass and substantial elevations of plasma and urine norepinephrine (15.4 nmol/L and 1022 µmol/mol creatinine, respectively); abnormal uptake of 123 I‐MIBG in the tumor led to PGL diagnosis. The patient was not able to have surgery because of substantial surgical risks; however, a combination of α‐ and β‐blockade was effective for blood pressure control. Array CGH revealed a deletion over 4.5 Mb, from the 1p telomere but excluding the SDHB region. Comprehensive mutational analysis of PGL‐associated genes ( RET, VHL, TMEM127, MAX, and SDHA/B/C/D ) was negative. These results indicate that the germline 1p36 deletion might be "1st hit" of tumor development, and PGL might be a novel complication of 1p36 deletion syndrome. © 2016 Wiley Periodicals, Inc.